The Function of the subject in the development of history teachers (Tzintzun, Revista de Estudios Históricos, 2016)
his article attempts to be a contribution to the training of history teachers. Itreviews various aspects of historical epistemology to explore its educationalpossibilities. he article insists on the idea that history should ofer symbolictissues that permit the student to give meaning to their experiences. For thisit is important to avoid certain barriers that arise from scientiic history andpedagogy, such as the foreclosure of the subject, overinterpretation, the abuseof rigid designators and the displacement of the desire of enjoyment. hearticle starts from a poststructuralist theoretical and conceptual frameworkand frequently uses Lacanian thought. It emphasizes the importance of thesubjective localization and indicates as its principal objective the didactics ofhistory to contribute to the emergence to an historic subject.
Keywords: history didactics; teacher development; epistemology of history; subject; psychoanalysis